PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN INTEGRASI USAHA PERKEBUNAN SAWIT DAN PETERNAKAN/PENGGEMUKAN SAPI DALAM MENJAGA KESEIMBANGAN PENDAPATAN PETANI - Syahril, Syahril; Saputra, Arie (Universitas Teuku Umar, 2024)
The decline in the price of palm oil FFB in the last two years has resulted in a decrease in the income of the Makmue Beusaree Farmers Group, sluggish business enthusiasm, and resulted in abandoned palm oil plantations. This program continues the design of fertilization technology in mountainous areas. Then there is the connection between this technology, and cow manure as a source of raw material for compost fertilizer. So, a combination of oil palm plantations and cattle farming is needed. The problem is, that partners still lack knowledge about managing cattle farms that are integrated with oil palm plantations. This service is carried out to provide basic conceptual knowledge regarding integrated agricultural skills and management. The approach used to answer partner problems is through training and monitoring. The types of training that will be carried out are techniques for determining the location for building and constructing cow sheds, training for raising cows, business financial management systems and techniques for obtaining cow seeds using the mawah system as well as systems and strategies for marketing cows and selling FFB that are more effective and profitable for farmers. The mentoring approach aims to increase and stabilize the income of oil palm farmers by making Gampoeng Teupin Panah, Kaway XVI District, West Aceh as a gampoeng assisted by the Faculty of Economics, Teuku Umar University